Carboranealkynyl‐Protected Gold Nanoclusters: Size Conversion and UV/Vis–NIR Optical Properties. (26th January 2021) - Wang, Jie; Wang, Zhao‐Yang; Li, Shi‐Jun; Zang, Shuang‐Quan; Mak, Thomas C. W.
Abstract: Structure evolution has become an effective way to assemble novel monolayer‐protected metal nanomolecules. However, evolution with alkynyl‐stabilized metal clusters still remains rarely explored. Herein, we present a carboranealkynyl‐protected gold nanocluster [Au28 (C4 B10 H11 )12 (tht)8 ] 3+ (Au28, tht=tetrahydrothiophene) possessing an open‐shell electronic structure with 13 free electrons, which was isolated by a facile self‐reduction method with 9‐HC≡C‐ closo ‐1, 2‐C2 B10 H11 as the two‐in‐one reducing and protecting agent. Notably, Au28 undergoes a complete transformation in methanol into a stable and smaller‐sized nanocluster [Au23 (C4 B10 H11 )9 (tht)6 ] 2+ (Au23 ) bearing 12 valence electrons and crystal‐field‐like split superatomic 1D orbitals. The transformation process was systematically monitored with ESI‐MS and UV/Vis absorption spectra. Au28 and Au23 both display optical absorption covering the UV/Vis–NIR range and NIR emission, which facilitates their potential application in the biomedical and photocatalytic fields. Abstract : A carboranealkynyl‐protected gold nanocluster Au28 possessing an open‐shell electronic structure with 13 valence electrons was isolated through a facile self‐reduction method in which it undergoes a complete transformation in methanol into a smaller‐sized cluster Au23 bearing 12 valence electrons and crystal‐field‐like split superatomic 1D orbitals. Au28 and Au23 both display optical absorption covering the UV/Vis–NIR range and NIR emission.